Удосконалення зерноочисної машини ЗОМ-3 з обґрунтуванням параметрів вивантажувача зерна - Драндалуш, Сергій Васильович; Drandalush, Serhii (ЦНТУ, 2023)
Метою роботи є підвищення ефективності роботи зерноочисної машини. Магістерська кваліфікаційна робота присвячена удосконаленню вивантажувача зерноочисної машини ЗОМ-3. В роботі проведено аналіз конструкцій транспортерів сільськогосподарського призначення, на основі якого виявлено ефективність інерційних транспортерів. Проведений теоретичний аналіз руху часток після сходу з решета зерноочисної машини дозволив отримати траєкторії їх польоту. Це дало змогу спроектувати вивантажувач. У інженерній частині здійснено обґрунтування основних конструктивних параметрів зерноочисної машини ЗОМ-3, продуктивністю 3 т/год. Креслення вивантажувача і елементів конструкції машини наведено у графічній частині магістерської роботи. The purpose of the work is to increase the efficiency of the grain cleaning machine. The master's thesis is devoted to the improvement of the unloader of the ZOM-3 grain cleaning machine. The paper analyzes the constructions of agricultural conveyors, on the basis of which the efficiency of inertial conveyors is revealed. The conducted theoretical analysis of the movement of particles after leaving the sieve of the grain cleaning machine made it possible to obtain the trajectories of their flight. This made it possible to design an unloader. In the engineering part, the substantiation of the main structural parameters of the ZOM-3 grain cleaning machine, with a productivity of 3 t/h, was carried out. Drawings of the unloader and the design elements of the machine are given in the graphic part of the master's work.
Improvement of the ZOM-3 grain cleaning machine with substantiation of the parameters of grain unloader
Keywords: зерноочисна машина; транспортер; інерційне вивантаження; частка; польот; grain cleaning machine; conveyor; inertial unloading; particle; flight